2013
DOI: 10.1245/s10434-013-3136-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil:Lymphocyte Ratio and Intraoperative Use of Ketorolac or Diclofenac are Prognostic Factors in Different Cohorts of Patients Undergoing Breast, Lung, and Kidney Cancer Surgery

Abstract: In these cohorts, these analyses show that NLR is a strong perioperative prognosis factor for breast, lung, and kidney cancers. In this context, intraoperative NSAIDs administration could be associated with a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 40 publications
5
118
0
3
Order By: Relevance
“…Several studies reported that high NLR value is always associated with inflammation, poor survival and a higher risk of distant metastasis [52,53]. The patients could be separated into two groups according to their NLR values.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that high NLR value is always associated with inflammation, poor survival and a higher risk of distant metastasis [52,53]. The patients could be separated into two groups according to their NLR values.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral blood absolute neutrophil count/absolute lymphocyte count ratio (ANC/ALC) or the neutrophil/lymphocyte ratio (NLR) at diagnosis is also a prognostic indicator in malignant tumors including breast cancer [45][46][47][48]. Furthermore, recent studies have revealed that NLR is a negative predictive factor of advanced esophageal cancer [49], stage III-IV gastric cancer [50], and breast cancer with ER/PR-positivity and HER2-negativity in the NAC setting [51].…”
Section: Discussionmentioning
confidence: 99%
“…For clinical application, we have to confirm the predictive role of the immediate postoperative NLR and examine whether the control of perioperative inflammation decreases the NLR and finally leads to good clinical outcomes. Forget et al [11,14] showed that the intraoperative administration of nonsteroidal anti-inflammatory drugs (NSAIDs) and lower NLR levels were associated with longer disease-free and overall survival in breast cancer. However, they did not show a direct correlation between the administration of NSAIDs and the lowering of the NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the prognostic value of the NLR at each stage and by several treatments in a variety of tumors, mostly in the gastrointestinal tract [5,6,7,8,9,10]. Although studies examining the NLR and breast cancer have been relatively small, they have consistently shown that preoperative inflammation measured with the NLR was associated with poor outcomes in breast cancer [11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%